Amyloid and its association with default network integrity in Alzheimer's disease. Issue 3 (14th December 2012) - Adriaanse, Sofie M.; Sanz‐Arigita, Ernesto J.; Binnewijzend, Maja A.A.; Ossenkoppele, Rik; Tolboom, Nelleke; van, Daniëlle M.E.; Wink, Alle Meije; Boellaard, Ronald; Yaqub, Maqsood; Windhorst, Albert D.; van der, Wiesje M.; Scheltens, Philip; et al.
<x xml:space="preserve">Abstract</x> The purpose of this study was to investigate the association between functional connectivity and β‐amyloid depositions in the default mode network (DMN) in Alzheimer's disease (AD), patients with mild cognitive impairment (MCI), and healthy elderly. Twenty‐five patients with AD, 12 patients with MCI, and 18 healthy controls were included in the study. Resting‐state functional magnetic resonance imaging was used to assess functional connectivity in the DMN. In parallel, amyloid burden was measured in the same subjects using positron emission tomography with carbon‐11‐labeled Pittsburgh Compound‐B as amyloid tracer. Functional connectivity of the DMN and amyloid deposition within the DMN were not associated across all subjects or within diagnostic groups. Longitudinal studies are needed to examine if amyloid depositions precede aberrant functional connectivity in the DMN. Hum Brain Mapp 35:779–791, 2014. © 2012 Wiley Periodicals, Inc.